Hierridin B Isolated from a Marine Cyanobacterium Alters VDAC1, Mitochondrial Activity, and Cell Cycle Genes on HT-29 Colon Adenocarcinoma Cells - Freitas S. (2016)
Background: Hierridin B was isolated from a marine cyanobacterium Cyanobium sp. strain and induced cytotoxicity selectively in HT-29 adenocarcinoma cells. The underlying molecular mechanism was not yet elucidated. Methods: HT-29 cells were exposed to the IC50concentration of hierridin B (100.2 μM) for 48 h. Non-targeted proteomics was performed using 2D gel electrophoresis and MALDI-TOF/TOF mass spectrometry. The mRNA expression of apoptotic and cell cycle genes were analyzed by real-time PCR. Automated quantification of 160 cytoplasm and mitochondrial parameter was done by fluorescence microscopy using CellProfiler software. Results: Proteomics identified 21 significant different proteins, which belonged to protein folding/synthesis and cell structure amongst others. Increase of VDAC1 protein responsible for formation of mitochondrial channels was confirmed by mRNA expression. A 10-fold decrease of cytoskeleton proteins (STMN1, TBCA) provided a link to alterations of the cell cycle. CCNB1 and CCNE mRNA were decreased two-fold, and P21CIP increased 10-fold, indicative of cell cycle arrest. Morphological analysis of mitochondrial parameter confirmed a reduced mitochondrial activity. Conclusion: Hierridin B is a potential anticancer compound that targets mitochondrial activity and function.